Complete Arcs in Projective Plane PG (2,11) Over Galois field - Fiadh, Mahmood S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, we construct complete (K, n)-arcs in the projective plane over Galois field GF (11), where 12 2 â‰¤ â‰¤ n ,by using geometrical method (using the union of some maximum(k,2)- Arcs , we found (12,2)-arc, (19,3)-arc , (29,4)-arc, (38,5)-arc , (47,6)-arc, (58,7)-arc, (68,6)-arc, (81,9)-arc, (96,10)-arc, (109,11)-arc, (133,12)-arc, all of them are complete arc in PG(2, 11) over GF(11).